Continuous 25-yr aerosol records at coastal Antarctica: Part 2: variability of the radionuclides 7Be, 10Be and 210Pb - Elsässer, Christoph; Wagenbach, Dietmar; Weller, Rolf; Auer, Matthias; Wallner, Anton; Christl, Marcus (Tellus. Series B, Chemical and physical meteorology, 2011)
We investigated the variability of 210Pb, 7Be and 10Be in coastal Antarctic aerosol samples based on continuous,monthly and annually resolved time series obtained from Neumayer Station over the period 1983 to 2008. Clear seasonal cycles peaking in the local summer half year stand out as a common feature of all three radionuclide records. Time series analyses suggest that significant multiannual changes are confined to a 4-6 yr periodicity resembling that of the Southern Annual Mode index in case of 210Pb and to the expected decadal solar cycle in case of the cosmogenic Be-isotopes. Both, changes in the meridional transport and surface inversion strength appear to drive the seasonal 210Pb cycle, which generally peaks in November. In contrast, stratospheric air mass intrusions are proved to be the main reason for the Be-isotopes seasonality. This finding is revealed by enhanced 10Be/7Be ratios occurring during late summer / early autumn broadly concurrently with the individual Be-isotopes and the 7Be/210Pb ratio. The 10Be and 7Be records clearly reflect the decadal, solar-modulated production signal but, for unknown reasons, they substantially differ in their detailed pattern. It is ruled out, that an excess 7Be production by solar energetic particles was responsible for this mismatch.
Elektronische Reproduktion der Druckausgabe
Gesehen am 12.04.2022
Im Zusatz zum Titel sind die Zahlen 7, 10 und 210 hochgestellt